2011
DOI: 10.1038/nn.2984
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic circuits mediate the reinforcement-related signals of striatal cholinergic interneurons

Abstract: Neostriatal cholinergic interneurons are believed to play an important role in reinforcement mediated learning and response selection by signaling the occurrence and motivational value of behaviorally relevant stimuli through precisely timed multiphasic population responses. An important problem is to understand how these signals regulate the functioning of the neostriatum. Here we describe the synaptic organization of a novel circuit that involves direct nicotinic excitation of GABAergic interneurons and enab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
333
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(361 citation statements)
references
References 50 publications
(79 reference statements)
25
333
3
Order By: Relevance
“…The majority of GABAergic interneurons in the striatum are parvalbumin-positive FS interneurons, which project primarily to the MSNs. Although FS interneurons are excited by nicotinic agonists (51), optogenetic activation of SChIs failed to increase FS interneuron spiking in one study (52). Additionally, optogenetic stimulation of SChIs in ChAT-ChR2 mice elicits both fast and slow inhibitory postsynaptic potentials in MSNs by nicotinic-mediated GABA release from dopamine projections to striatum (53) and neuropeptide Y-expressing neurogliaform GABAergic interneurons, resulting in inhibition of MSNs (52).…”
Section: M1 Superficialmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of GABAergic interneurons in the striatum are parvalbumin-positive FS interneurons, which project primarily to the MSNs. Although FS interneurons are excited by nicotinic agonists (51), optogenetic activation of SChIs failed to increase FS interneuron spiking in one study (52). Additionally, optogenetic stimulation of SChIs in ChAT-ChR2 mice elicits both fast and slow inhibitory postsynaptic potentials in MSNs by nicotinic-mediated GABA release from dopamine projections to striatum (53) and neuropeptide Y-expressing neurogliaform GABAergic interneurons, resulting in inhibition of MSNs (52).…”
Section: M1 Superficialmentioning
confidence: 99%
“…Although FS interneurons are excited by nicotinic agonists (51), optogenetic activation of SChIs failed to increase FS interneuron spiking in one study (52). Additionally, optogenetic stimulation of SChIs in ChAT-ChR2 mice elicits both fast and slow inhibitory postsynaptic potentials in MSNs by nicotinic-mediated GABA release from dopamine projections to striatum (53) and neuropeptide Y-expressing neurogliaform GABAergic interneurons, resulting in inhibition of MSNs (52). However, nicotinic receptors generally quickly desensitize and, thus, we did not expect GABAergic blockade of MSN spiking to continue through the 5 s of stimulation used in our current study.…”
Section: M1 Superficialmentioning
confidence: 99%
“…ACh was shown to depolarize FSIs directly through nAChRs and attenuate their GABAergic inhibition on MSNs by presynaptic muscarinic acetylcholine receptors (mAChR) on FSI terminals (Koos and Tepper 2002). More recently, a study showed that activation of a novel inhibitory NPY-neurogliaform by nicotinic synaptic inputs from cholinergic interneurons contributes to slow inhibitory currents in MSNs (English et al 2011). …”
Section: Modulation Of Interneurons and Msns By Acetylcholinementioning
confidence: 99%
“…Neurons within the NAc comprises a majority (B95%) of medium spiny neurons (MSNs) and heterogeneous populations of interneurons, including fast-spiking interneurons (FSIs), GABAergic interneurons, and cholinergic interneurons, which provide functional feedforward inhibition to MSN populations (English et al, 2012;Gage et al, 2010;Koos and Tepper, 1999). These neuronal groups are important for rewarding and aversive motivational processing.…”
Section: Introductionmentioning
confidence: 99%